ASOSIASI JENIS BURUNG DI KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Raungku, Martinus A; Toknok, Bau; Sustri, Sustri (Universitas Tadulako)
thing as an implication is the high endemicity because the eastern region of Indonesia consists of more clusters of small islands, making many species isolated and ultimately having to adjust to their habitat and environment. Association is the interdependence between species and other types. Both animals and plants from the simplest to the high-rise ones. The purpose of the study was to find out the types of birds and their associations found in the Forest Education Area of Tadulako University, Bolano Lambunu District, Parigi Moutong Regency. This research was conducted for 3 months, from April to June 2016. The method of data collection in this study included the collection of primary data and secondary data. In this study, the transect pathway method is used which is a method used in which the observer walks by following the direction and location of the center line of the transect slowly while recording the types of birds encountered, both directly (visually) and indirectly. This observation is done by determining the observation points as many as 10 points and placed on the left and right transect lines along the 500 meters. In this study one transect line was used. The Forest Education Area of Tadulako University, Bolano Lambunu District, Parigi Moutong Regency, there are 17 species of birds that are included in 11 families. there are 8 species of birds which are Sulawesi endemics found in the study site. To find out whether there are associations between the two types, a comparison between Chi-Square counts XÂ² count with XÂ² tables at the free degree = 1. Of the 17 species of birds found in the study location, 11 species are categorized as associations because they have x2 count values > 3.841 and there are 5 types of birds which are categorized as not associated because they have a value of x2 calculated <3.841.Keywords: Bird Association, Educational Forest, Bolano Lambunu